Self-assembly and electronic effects of Er3N@C80 and Sc3N@C80 on Au(111) and Ag/Si(111) surfaces - Nörenberg, C; Leigh, D; Cattaneo, D; Porfyrakis, K; Bassi, A; Casari, C; Passoni, M; Owen, J; Briggs, G (2008)
We have investigated self-assembled island formation, molecular detail and interesting contrast reversal effects for Er3N@C80 and Sc3N@C80 on Au(111) and Ag/Si(111) surfaces using variable temperature scanning tunnelling microscopy (STM) and spectroscopy (STS). The trinitride containing fullerenes have been evaporated onto Ag-passivated Si(111) at room temperature and self-assembled into close-packed 2-D islands. Gentle annealing at 200 - 300 °C is required for the formation of close-packed islands with 20 - 50 nm diameter on the Au(111) surface. Variable-voltage STM reveals bias-dependent contrast anomalies within the islands, and at low temperatures (< 90K), intra-molecular resolution of the fullerenes has been achieved. STS measurements indicate that the bright/dark anomalies may be caused by different electron densities of states for the "normal" and "anomalous" fullerenes. ©2008 IOP Publishing Ltd.